If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying X + -7 + -7x = 14 + -3x Reorder the terms: -7 + X + -7x = 14 + -3x Solving -7 + X + -7x = 14 + -3x Solving for variable 'X'. Move all terms containing X to the left, all other terms to the right. Add '7' to each side of the equation. -7 + X + 7 + -7x = 14 + 7 + -3x Reorder the terms: -7 + 7 + X + -7x = 14 + 7 + -3x Combine like terms: -7 + 7 = 0 0 + X + -7x = 14 + 7 + -3x X + -7x = 14 + 7 + -3x Combine like terms: 14 + 7 = 21 X + -7x = 21 + -3x Add '7x' to each side of the equation. X + -7x + 7x = 21 + -3x + 7x Combine like terms: -7x + 7x = 0 X + 0 = 21 + -3x + 7x X = 21 + -3x + 7x Combine like terms: -3x + 7x = 4x X = 21 + 4x Simplifying X = 21 + 4x
| 20=-2y+4x | | x*11+22=x*2+247 | | 2/3x-3x | | 7b-3-8=2-7b+b | | 3x^(3/5)=81 | | 12x+14=91 | | 12/12-1/13 | | 1+6b=7+8b-5b | | 4x-5+15=180 | | 5a^6b^2-15a^3b^5/(5a^5b^3) | | y=3/0 | | 952=(26+2x)(20+2x) | | 5+78x=52x+17 | | h+c=24 | | -7x-6x=-2x | | 8x+2+74=180 | | 8/10-5/7 | | -4+3t=-12+13t | | 3x+1=3(3x+1)-5 | | 2/5d-6/5=30 | | =x(95-4x) | | 5-m=-11-5m | | 4z^-1/8(3z^7-z^-1/8) | | 2x^2+8x+3x+12=0 | | 4n+8-4n=14+6n | | (5a^6b^2-15a^3b^5)/(5a^5b^3) | | 56+x+6=180 | | 144=x+2+x+3 | | 3x+5y=65 | | 6-6n=-6-2n | | 7t-3=2(t+1)+2 | | 3x+4x-5=37 |